Self‐awareness of executive dysfunction in Huntington's disease: Comparison with Parkinson's disease and cervical dystonia. Issue 1 (21st January 2013) - Sitek, Emilia J.; Sołtan, Witold; Wieczorek, Dariusz; Schinwelski, Michał; Robowski, Piotr; Harciarek, Michał; Guzińska, Katarzyna; Sławek, Jarosław
<x xml:space="preserve">Abstract</x> This study assessed self‐awareness of executive deficits in patients with Huntington's disease (HD) in comparison to patients with Parkinson's disease (PD) and with cervical dystonia (CD). Eighty‐nine patient–proxy pairs participated in the study (23 with HD, 25 with advanced PD, 21 with mild PD and 20 with CD). Executive function was assessed with the Stroop test and the Dysexecutive Questionnaire. Insight into executive impairment in HD is mildly affected, when compared to PD and CD.